Design of Fe3O4@SiO2@mSiO2-organosilane carbon dots nanoparticles: Synthesis and fluorescence red-shift properties with concentration dependence. (5th August 2018) - Li, Xiaolei; Wang, Wei; Li, Qianli; Lin, Han; Xu, Yue; Zhuang, Lin
Abstract: Organosilane-functionalized carbon dots (SiCDs) immobilized silica composite nanoparticles (Fe3 O4 @SiO2 @mSiO2 -SiCDs) with dually emissive properties have been prepared by a modified sol-gel method. Such Fe3 O4 @SiO2 @mSiO2 -SiCDs nanoparticles solution exhibits blue light emission with a maximum wavelength of 470 nm at lower concentrations, and red-shifts to yellow-green light emission with maximum wavelength of 565 nm at higher concentrations, which is different with traditional carbon dots composite materials displaying strong emission only in the blue-light region. The SiCDs are immobilized in the outer mesoporous silica layer by covalent bonds via proper blending ration, which enables the nanoparticles solution to possess excellent fluorescence stability. The Fe3 O4 @SiO2 @mSiO2 -SiCDs nanoparticles show good stability, high surface area (483.19 m 2 /g), high saturation magnetization (22.1 emu/g) and low remanence (0.217 emu/g). When the concentration of nanoparticles solution is increased, the distance between the nanoparticles decreases and exhibits the concentration-mediated scattering phenomena, which result in the red-shift of fluorescent peaks. The specific structure of the Fe3 O4 @SiO2 @mSiO2 -SiCDs nanoparticles and the concentration-mediated scattering phenomena play key roles in the red-shift appearing. Graphical abstract: Unlabelled Image Highlights: Organosilane-functionalized carbon dots immobilized silica composite nanoparticles were prepared by modified sol-gel method. Preparation parameters and influence factors of synthesis were investigated by different characterization techniques. The composite nanoparticles show good stability, excellent dispersity and a mesoporous structure. The nanoparticles solution exhibits blue emission at lower concentrations and yellow-green emission at higher concentrations. The specific structure of composite nanoparticles and the concentration-mediated scattering play key roles in the red-shifts.